Pengaruh OCB dan Motivasi Kerja Terhadap Kinerja Karyawan PT. Batara Titian Kencana (Xtrans) Cabang Menteng - Jakarta Pusat - Basri, Hasan; Nabilah, Lily (Universitas Mohammad Husni Thamrin, 2020)
Effect Of Organizational Citizenship Behavior And Employee Motivation To Employees Performance PT Batara Titian Kencana (Xtrans) Branch Menteng - Jakarta Pusat. Based on the results of research conducted on Organizational Citizenship Behavior (OCB) and Work Motivation on Employee Performance of PT Batara Titian Kencana (XTRANS) Menteng Branch - Central Jakarta, the writer can draw the following conclusion: 1. Organizational Citizenship Behavior (OCB) and Employee Performance PT Batara Titian Kencana Xtrans showed a correlation coefficient of 0.736 which means a strong influence between OCB on employee performance, while the diversity of respondents based on OCB variables that have been studied by the authors are dominated by indicators to colleagues who do not understand I am willing to tell about how the use of work tools yag well and true in carrying out all the work we do. 2. Motivation and Performance of employees of PT Batara Titian Kencana Xtrans showed a correlation coefficient of 0.711 which means a strong influence between work morivation variable on employee performance, while the diversity of respondents based on motivation variables that have been studied by the writer dominated by indicators I always try to improve work productivity . 3. In the result of correlation analysis between Organizational Citizenship Behavior (OCB), and Work Motivation to Employee Performance is strong and significant, it is shown figure in table R = 0,736. So it can be concluded that there is a strong influence between OCB variables work motivation together to employee performance. That is, employees can provide the best for companies or organizations, thus will affect both the performance of the employees themselves.Â Keywords: Organizational Citizenship Behavior and Employee Motivation To EmployeesPerformance